Application of MRI-based Finite Element Modeling and Analysis in Periacetabular Osteotomy - ZHOU Tianli; ZHANG Dian; WU Jizhi; JIA Huihui; CHANG Yan; SHENG Mao; YANG Xiaodong (Chinese Journal of Magnetic Resonance, 2023)
Periacetabular osteotomy (PAO) is a surgical procedure to correct acetabular orientation in developmental dysplasia of the hip (DDH). In this work, magnetic resonance imaging-based finite element models of hip joint were introduced to perform virtual surgery planning for patients with DDH. The optimal position of acetabulum following PAO was determined by analyzing the peak contact pressure and contact area between the femoral and pelvic cartilage when the acetabulum rotated from the original center edge (CE) angle in increments of 5°. Furthermore, with finite element analysis, we simulated joint movements in both the preoperative model and the planned model with the optimal position for the six cases. A comparison between the preoperative and planned models for all scenarios was made. The outcomes of finite element analysis revealed that the optimal position of acetabulum was at a CE angle of 20°. In all evaluated scenarios, the planned model showed lower peak contact pressure and larger contact area than the preoperative model did. The efficacy of virtual surgery planning was thus validated from a biomechanical perspective.